2020
DOI: 10.31234/osf.io/wxe2n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring the psychological impact of the COVID-19 pandemic in the general population: an overview of the context, design and conduct of the COVID-19 Psychological Research Consortium (C19PRC) Study

Abstract: The COVID-19 Psychological Research Consortium (C19PRC) Study aims to assess and monitor the psychological and social impact of the coronavirus (COVID-19) pandemic in the general population, using longitudinal surveys and mixed-methods studies in multiple countries. The first strand of the study, an internet-based panel survey, was launched in the UK in March 2020 during the earliest stages of the pandemic in that country (hereafter referred to as C19PRC-UKW1). This paper describes (1) the development, design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 85 publications
2
46
0
1
Order By: Relevance
“…Subsequent checks ensured that the participants were also representative of the population in terms of voting history, number of people in household and other important demographic characteristics. 9 Participants were recruited from the four countries of the UK, proportional to their relative population sizes: England (86.9 %), Wales (3.1 %), Scotland (7.8 %), Northern Ireland (2.3 %). The mean age of the sample was 45.44 years (median = 45.00, s.d.…”
Section: Recruitment and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent checks ensured that the participants were also representative of the population in terms of voting history, number of people in household and other important demographic characteristics. 9 Participants were recruited from the four countries of the UK, proportional to their relative population sizes: England (86.9 %), Wales (3.1 %), Scotland (7.8 %), Northern Ireland (2.3 %). The mean age of the sample was 45.44 years (median = 45.00, s.d.…”
Section: Recruitment and Participantsmentioning
confidence: 99%
“…8 Here, we report initial findings from the first wave of a longitudinal, multi-wave survey of the social and psychological effects of COVID-19 on the UK population, conducted by researchers in seven UK and Irish universities (the COVID-19 Psychological Research Consortium). 9 Of note, in a mirror study with similar methodology, we recently reported the social and psychological effects of COVID-19 on the population of the Republic of Ireland. 10 The primary aim of this study was to assess the levels of anxiety, depression and traumatic stress, based on validated selfreport measures, in a large, representative community sample during an early stage of the pandemic, between 23 and 28 March 2020.…”
mentioning
confidence: 99%
“…The first UK survey took place a week prior to the Irish survey (7) and found that 22.1% (95% CI = 20.31, 23.93) of people screened positive for depression, 21.6% (95% CI = 19.83, 23.42) screened positive for generalized anxiety disorder (GAD), and 27.8% (95% CI = 25.80-29.71) screened positive for GAD or depression. Furthermore, screening positive for GAD or depression was associated with younger age, having more than one child in the home, reporting lower income levels in 2019, experiencing a loss of income due to the COVID-19 pandemic, having an underlying health condition (lung disease, heart disease or diabetes), having a loved one with an underlying health condition (lung disease, heart disease or diabetes), having a confirmed or suspected infection of COVID-19 and having a moderate or high level of perceived risk of infection of COVID-19 over the next month (8).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the studies conducted across the globe have been investigated the psychological impacts of COVID-19 pandemic predominantly focused on health care workers and patients [26][27][28].…”
Section: Introductionmentioning
confidence: 99%